Applied Chemistry A Textbook for Engineers and Technologists - Roussak, Oleg; Gesser, H. D. (Springer US : Imprint: Springer, 2013)
The second edition of Gesser's classic Applied Chemistry includes updated versions of the original 16 chapters plus two new chapters on semiconductors and nanotechnology. This textbook introduces chemistry students to the applications of their field to engineering design and function across a wide range of subjects, from fuels and polymers to electrochemistry and water treatment. Each chapter concludes with a reading list of relevant books and articles as well as a set of exercises which include problems that extend the topics beyond the text. Other supplements to the text include a laboratory section with step-by-step experiments and a solutions manual for instructors.